Answer:
Explanation:
The given equation is
(x – 4)(x – 3) = 0
We would open the parenthesis by multiplying each term in the first parenthesis by each term in the second parentheses. It becomes
x^2 - 3x - 4x + 12 = 0
x^2 - 7x + 12
We would apply the method of factorization by looking for two numbers such that, when they are added or subtracted, the result would be -7x and when they are multiplied, the result would be 12x^2. The two numbers are -3x and - 4x. Therefore
x^2 -3x - 4x + 12 = 0
x(x - 3) - 4(x - 3) = 0
(x - 3)(x - 4) = 0
x - 3 = 0 or x - 4 = 0
x = 3 or x = 4
So let us check
if x = 3,
(3 – 4)(3 – 3) = 0
- 1×0 = 0
If x = 4
(4 – 4)(4 – 3) = 0
0×1 = 0